Activation of the Rab7 GTPase by the MON1-CCZ1 Complex Is Essential for PVC-to-Vacuole Trafficking and Plant Growth in Arabidopsis . Issue 5 (13th May 2014) - Cui, Yong; Zhao, Qiong; Gao, Caiji; Ding, Yu; Zeng, Yonglun; Ueda, Takashi; Nakano, Akihiko; Jiang, Liwen
Abstract : This work identifies the Arabidopsis MON1 and CCZ1 proteins as forming a dimeric complex that functions as a Rab5 effector and a Rab7 GEF to mediate Rab5-to-Rab7 conversion on PVCs. Arabidopsis Rab7 and mon1 mutants contained enlarged PVCs and fragmented vacuoles, and exhibited defects in vacuolar trafficking and retarded-growth phenotypes. Abstract: Rab GTPases serve as multifaceted organizers during vesicle trafficking. Rab7, a member of the Rab GTPase family, has been shown to perform various essential functions in endosome trafficking and in endosome-to-lysosome trafficking in mammalian systems. The Arabidopsis thaliana genome encodes eight putative Rab7 homologs; however, the detailed function and activation mechanism of Rab7 in plants remain unknown. Here, we demonstrate that Arabidopsis RABG3f, a member of the plant Rab7 small GTPase family, localizes to prevacuolar compartments (PVCs) and the tonoplast. The proper activation of Rab7 is essential for both PVC-to-vacuole trafficking and vacuole biogenesis. Expression of a dominant-negative Rab7 mutant (RABG3f T22N ) induces the formation of enlarged PVCs and affects vacuole morphology in plant cells. We also identify Arabidopsis MON1 (MONENSIN SENSITIVITY1) and CCZ1 (CALCIUM CAFFEINE ZINC SENSITIVITY1) proteins as a dimeric complex that functions as the Rab7 guanine nucleotide exchange factor. The MON1-CCZ1 complex also serves as the Rab5 effector to mediate Rab5-to-Rab7 conversion on PVCs. Loss of functional MON1 causes the formation of enlarged Rab5-positive PVCs that are separated from Rab7-positive endosomes. Similar to the dominant-negative Rab7 mutant, the mon1 mutants show pleiotropic growth defects, fragmented vacuoles, and altered vacuolar trafficking. Thus, Rab7 activation by the MON1-CCZ1 complex is critical for vacuolar trafficking, vacuole biogenesis, and plant growth.